1986
DOI: 10.3164/jcbn.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Lipid Peroxidation in Rat Gastric Mucosal Lesions Induced by Water-Immersion Restraint Stress

Abstract: SummaryThe role of lipid peroxidation in the pathogenesis of gastric ulcer was investigated in a rat model produced by water-immersion restraint stress. After the immersion of rats in 23°C water with restraint, blood flow of the gastric wall was significantly decreased and hemorrhagic erosions were seen in the body of the stomach. Thiobarbituric acid-reactive substances, an index of lipid peroxidation, in the gastric mucosa were significantly increased after the stress. These results suggest that lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Oxygen-free radicals and lipid peroxidation have been reported to participate in the formation of gastric mucosal lesions caused by a variety of ulcerogenic stimuli, such as ischemia-reperfusion (Perry et al, 1986) and several kinds of stress (Ito and Guth, 1985;Yoshikawa et al, 1986;. They have been implicated in the pathogenesis of ethanol-induced gastric mucosal injury as well (Pihan et al, 1987), because two enzymatic antioxidants, superoxide dismutase, and catalase reduced the gastric mucosal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen-free radicals and lipid peroxidation have been reported to participate in the formation of gastric mucosal lesions caused by a variety of ulcerogenic stimuli, such as ischemia-reperfusion (Perry et al, 1986) and several kinds of stress (Ito and Guth, 1985;Yoshikawa et al, 1986;. They have been implicated in the pathogenesis of ethanol-induced gastric mucosal injury as well (Pihan et al, 1987), because two enzymatic antioxidants, superoxide dismutase, and catalase reduced the gastric mucosal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, oxygen-free radicals are involved in the process of formation of gastric mucosal lesions that are induced by a variety of ulcerogenic stimuli such as ischemia-reperfusion (Perry et al, 1986), several kinds of stress (Ito and Guth, 1985;Yoshikawa et al, 1986;, and ethanol (Pihan et al, 1987), and antioxidants can afford gastric cytoprotection. In ad-dition, it has been reported that intravenous administration of MT-II (2.5 mg/kg, 1.0 mg/kg, iv) suppresses the formation of water-immersion stress-induced and HCl-ethanol-induced gastric mucosal lesions in rats (Mimura et al, 1988).…”
mentioning
confidence: 99%
“…On the other hand, it has been reported that lipid peroxidation plays a significant role in the pathogenesis of gastric mucosal lesions induced by stress [4] or burn shock [5].…”
Section: Discussionmentioning
confidence: 99%
“…Yoshikawa et al (1986) reported that TBA-reactive substances, an indirect index of lipid peroxidation, were significantly increased in gastric mucosa after CWIR stress in rats. They suggested that lipid peroxidation may play a role in the pathogenesis of gastric mucosal lesions.…”
Section: Ulcer Indexmentioning
confidence: 99%
“…Although numerous studies have been undertaken to determine the relationship between gastric mucosal lesions and lipid peroxidation in CWIR stress, direct evidence for such a relationship is still lacking. In previous studies (Yoshikawa et al 1986;Tarnasky et al 1990), the link between gastric mucosal lesions and tissue lipid peroxidation could not be adequately assessed because the thiobarbituric acid (TBA) test commonly employed in such experiments is not specific for lipid peroxides. colleagues (1993, 1994) have recently developed a new, sensitive and selective assay for phospholipid hydroperoxides using high performance liquid chromatography (HPLC) combined with chemiluminescence (CL) detection.…”
mentioning
confidence: 99%